Effectiveness of Pregnancy Education Application with Mental Health Approach (PEA-MH) on Pregnant Women - Niasty Lasmy Zaen; Saddiyah Rangkuti; Muslimah Pase (GLOBAL HEALTH SCIENCE GROUP, 2025)
Maternal mental health is a crucial determinant that influences the quality of pregnancy, childbirth, and child development. Nevertheless, many pregnant women remain vulnerable to anxiety, stress, and depression due to limited access to adequate information and health services. This study aims to evaluate the effectiveness of the Pregnancy Education Application with Mental Health Approach (PEA-MH) as a digital educational medium to support maternal mental health. A descriptive qualitative design with quantitative evaluation was employed, involving 25 pregnant women selected through purposive sampling in Tanjung Morawa District, North Sumatra. Data were collected through initial observations, a digital service effectiveness questionnaire, and semi-structured interviews. The collected data were analyzed using thematic analysis for qualitative findings and descriptive statistical analysis for quantitative data. The results indicated that PEA-MH was effective in increasing knowledge, reducing anxiety, and strengthening maternal readiness for childbirth, although challenges remained, particularly regarding limited interactive features and unstable internet connectivity. In conclusion, PEA-MH demonstrates potential as a digital health innovation to support maternal health services, with further recommendations directed toward enhancing interactivity, ensuring evidence-based content, and strengthening digital infrastructure for sustainable implementation.